Development of Interactive E-Books Oriented Towards Science Literacy Skills on Immune System Material - Kartika, Dika; Uno, Wirnangsi Din; Dama, Lilan; Ibrahim, Mustamin; Solang, Margaretha; Hasan, Ani M. (Fakultas Keguruan dan Ilmu Pendidikan Universitas Labuhanbatu, 2023)
This research aims to get interactive e-book learning media oriented to science literacy skills on immune system material. The e-book learning criteria produced in this study have been valid, practical, and effective. This type of research is development research that uses 4D models (Define, Design, Develop, Disseminate). This study used 6 instruments, namely: interview instruments, validation instruments, student response instruments, learning implementation assessment instruments, student activity assessment instruments, and learning outcome assessment instruments (pre-test and post-test). The results found that the validity test based on the assessment results of validators of material experts, media experts, question experts and teachers obtained x ̅ scores of 98%, 97%, 93.33% and 91.33% (very good) respectively. The practicality test for the results of learning implementation in this study was the first meeting and the second meeting got a score of x ̅ 97%, the results of student activities in the first and second meetings got a score of x ̅ respectively 87%, and 90%, and the results of student responses in this study got a score x ̅ is 86% (all of those results belong to the